6(4)+-25=7+-2(4)

Simple and best practice solution for 6(4)+-25=7+-2(4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4)+-25=7+-2(4) equation:


Simplifying
6(4) + -25 = 7 + -2(4)

Multiply 6 * 4
24 + -25 = 7 + -2(4)

Combine like terms: 24 + -25 = -1
-1 = 7 + -2(4)

Multiply -2 * 4
-1 = 7 + -8

Combine like terms: 7 + -8 = -1
-1 = -1

Add '1' to each side of the equation.
-1 + 1 = -1 + 1

Combine like terms: -1 + 1 = 0
0 = -1 + 1

Combine like terms: -1 + 1 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (8x+25)+(3x+75)=180 | | (2x-7)-(x-6)=14 | | 3x-3-24=4x-4 | | 2x-11=3x-7 | | y=16x+16+19 | | 1x-9=-27 | | 2+2=m | | 4x+7-7x=14 | | 2x+8=x-20 | | 9(y+3)=12(y+5) | | -6=7+x | | 12x^2-12x^3= | | 1.5y-0.2y= | | 9x-14+3(x-8)=7 | | 27-11p-13p=-9 | | 12+11y=-18-4y | | u-9=-5 | | 5-(-4)=3(n+2) | | 12x^2+25x=7 | | g^2+6g-16=0 | | 3x+-4=2x+8 | | 7x^2+x-21=0 | | u-9=-1 | | .5x+6x+2=3+6 | | -(7-x)=x+2 | | 15x=6(x-9) | | 4(-3x+1)=-10x(x-4)-14x | | 10-(10-y)=21-2y | | (9x+3x)-(4x^2+8x)= | | 11=u-1 | | (8x^2+1)+(12x^2+6)=0 | | t^2+25t-24=0 |

Equations solver categories